Pendidikan Karakter dan Pergeseran Sosiopsikologis Penganut Aliran Tarekat Qadiriyahwanaqsabandiyah Surabaya - Jainudin, Jainudin (JOIES (Journal of Islamic Education Studies), 2016)
This article discusses the character education and socio-psichological shift among the followers of Tarekat QadiriyahwaNaqsabandiyah Surabaya. Tarekat QÄdiriyyahwaNaqshabandiyyah is a tarekat which combines QÄdiriyyahwaNaqshabandiyyah carried out by Syekh Aá¸¥mad Khaá¹Ä«b al-SambasÄ« from Kalimantan who practiced dhikr khafÄ« and jahr by reciting LÄilÄha illÄ AllÄh. The tarekat has prescribed several teachings, such as the perfectness of sulÅ«k, the adab of the adherents, dhikr, and murÄqabah. Some of its basic tenets are: dhikr, murÄqabah, rÄbiá¹ah, performing sharÄ«â€˜ah, doing optional worships, showing waraâ€˜ and zuhd behaviors, khalwah andâ€˜uzlah. Among its rites, moreover, are: bayâ€˜ah and dhikr. This article reveals that the adherents of QÄdiriyyahwaNaqshabandiyyah turn out to have better socio-psychological characters, such as patience, endurance, sincerity, satisfaction, and persistence in doing pure as well as social worships than they were before.Those are some indicators of good characters. In other words, the article concludes that the teachings, tenets, and rites of the tarekat can be used as a media to build noble characters of the society by undergoing socio-psychological changes in their daily behaviors.